Polyvinyl alcohol composition and preparation method thereof, and polyvinyl alcohol film and preparation method thereof
By pre-softening, blending, plasticizing and extruding polyvinyl alcohol compositions in the extruder, the problem that polyvinyl alcohol is difficult to achieve continuous and stable melt extrusion-bidirectional stretch forming is solved, and the efficient, economical and environmentally friendly preparation of polyvinyl alcohol films is achieved to meet the needs of green packaging materials.
Patent Information
- Application Number
- CN202311077697.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to achieve continuous and stable melt extrusion-bidirectional stretch forming of polyvinyl alcohol, resulting in complex processes, long production cycles, large energy consumption, high costs, and failure to fully exert product performance.
Polyvinyl alcohol composition is obtained by mixing polyvinyl alcohol, plasticizer, melt flow modifier and stabilizer in a specific proportion, and pre-softening, blending, plasticizing, extruding in an extruder, followed by air cooling and pelleting. The composition can prepare polyvinyl alcohol films by melt extrusion continuous bidirectional stretching.
The simple, efficient and fast melt processing of polyvinyl alcohol is achieved, and the film with excellent performance is prepared to meet the needs of green packaging materials, and the process is simplified, avoiding the complex process of casting the sheet first and then stretching.
Smart Images

Figure BDA0004413648660000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular, relates to a polyvinyl alcohol composition and a preparation method thereof, a polyvinyl alcohol film and a preparation method thereof. Background Art
[0002] Polyvinyl alcohol (PVA) is a polymer with excellent comprehensive properties and strong hydrogen bonding properties of multiple hydroxyls. It has excellent mechanical properties, oxygen barrier properties, and organic solvent resistance, and is antistatic. It can be photo-oxidatively degraded and biodegraded under certain conditions, and has potential applications in the field of high-end green packaging. However, PVA has a high degree of crystallinity and strong intramolecular and intermolecular hydrogen bonding, which leads to its high melting point of about 220°C. It is not yet melted, but dehydrated and etherified at 160°C. Degradation occurs during the melting process, and its film products are difficult to prepare by melt processing. Most of the existing commercially available films are formed by solution casting, mainly polyvinyl alcohol with a degree of alcoholysis of less than 88 mol% that is soluble in water at room temperature. Not only are the processes complicated, the production cycle is long, the energy consumption is large, and the cost is high, but the products are limited to the fields of embroidery substrates, laundry beads packaging, etc., which is not conducive to the excellent material properties of polyvinyl alcohol, and greatly limits the promotion and application of polyvinyl alcohol films.
[0003] In order to realize the melt processing of polyvinyl alcohol, domestic and foreign researchers have conducted a lot of research, and the technology is mainly concentrated in grafting, copolymerization, blending and plasticization modification. The process of grafting and copolymerization modification is relatively complicated, with large industrial investment and great production difficulty; the modification effect of blending modification is often not obvious; plasticization modification is relatively simple and has been studied more. It mainly achieves melt processing by adding some small molecular compounds into the polyvinyl alcohol crystal area, destroying the regularity of the polyvinyl alcohol crystal area, reducing its crystallization, and realizing its melt processing. Commonly used ones are water, propylene glycol, ethanolamine, formamide and metal salts.
[0004] However, the modification process is mostly to mix polyvinyl alcohol and each modified component in a high-speed mixer at a certain temperature, and then prepare melt-processable polyvinyl alcohol through extrusion granulation by a single screw extruder, and then melt-extrude into a film sheet, and then stretch it. The modification cycle is long, and film formation and stretching are separated, and continuous molding cannot be performed. For example, patent document CN106189010B, polyvinyl alcohol, plasticizer, soft water, processing aid and cross-linking agent are mixed evenly under stirring and warmed to 30-90°C, and kept for 1 / 6 to 10 hours, and then melt-extruded and pelletized by an extruder to obtain a melt-processable polyvinyl alcohol resin, and then the resin is extruded into a thin sheet, and then biaxially stretched to form a film. Patent document CN109721904A, polyvinyl alcohol, plasticizer, non-conductive functional filler, lubricant and optional auxiliary agent are mixed at a temperature of 50-90°C for 0.5 to 4h, and then melt-extruded and cast to obtain a polyvinyl alcohol casting, and then biaxially stretched to form a film.
[0005] Therefore, it is urgent to establish a simple and efficient melt-processable polyvinyl alcohol composition preparation technology to achieve its continuous and stable melt extrusion-biaxial stretching molding. Summary of the invention
[0006] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a polyvinyl alcohol composition and a preparation method thereof and a polyvinyl alcohol film and a preparation method thereof. The polyvinyl alcohol composition can meet the requirements of melt extrusion continuous biaxial stretching, quickly produce a polyvinyl alcohol film, and the film has excellent performance.
[0007] A first aspect of the present invention provides a polyvinyl alcohol composition, which comprises polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer;
[0008] In parts by weight, the content of the polyvinyl alcohol is 65 to 85 parts, the content of the plasticizer is 12 to 30 parts, the content of the melt flow modifier is 2.5 to 4 parts by weight, and the content of the stabilizer is 0.5 to 1 part by weight.
[0009] The second aspect of the present invention provides a method for preparing the above-mentioned polyvinyl alcohol composition, the preparation method comprising:
[0010] 1) uniformly mixing polyvinyl alcohol, a melt flow modifier and a stabilizer to obtain a mixture;
[0011] 2) The mixture and the plasticizer are added into an extruder to complete pre-softening, blending, plasticizing, and extrusion, and then air-cooled and pelletized to obtain a polyvinyl alcohol composition.
[0012] The third aspect of the present invention provides a method for preparing a polyvinyl alcohol film. The film is prepared from the polyvinyl alcohol composition by melt extrusion and continuous biaxial stretching.
[0013] A fourth aspect of the present invention provides a polyvinyl alcohol film, which is prepared by the above-mentioned method for preparing the polyvinyl alcohol film.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1. All components used in the polyvinyl alcohol composition of the present invention are non-toxic, harmless, and environmentally friendly, and can meet the current market demand for green packaging materials.
[0016] 2. The particle size of the polyvinyl alcohol granules used in the polyvinyl alcohol composition of the present invention is 0.3 mm to 0.8 mm, which is conducive to uniform mixing with the melt flow modifier and stabilizer and pre-softening in a twin-screw extruder.
[0017] 3. The present invention adopts online plasticization, which is simple, efficient and fast. Through dynamic plasticization in a twin-screw extruder, the plasticization effect is better, the melt viscosity of the obtained composition is lower, and it has good reprocessing fluidity. At the same time, it avoids the problems of long time required for mixing and standing at a certain temperature in a high mixer, high energy consumption, etc., and is clean and environmentally friendly.
[0018] 4. The polyvinyl alcohol composition of the present invention has excellent melt flow properties, a melt index of 10 to 30 g / 10 min (5 kg, 170° C.), a high pressure capillary melt viscosity of 100 to 500 Pa·S (shear rate 1000S -1 , 170℃), which meets the needs of continuous melt extrusion-biaxial stretching. No special equipment is required. Continuous extrusion and biaxial stretching can be carried out directly on conventional single-screw melt extrusion casting-biaxial stretching equipment. The process is simpler and avoids the complicated process of casting and then stretching.
[0019] 5. The film preparation method of the present invention is simple, efficient, economical and environmentally friendly, and can be used to prepare electrical appliance packaging, high-end clothing packaging, food barrier packaging film, etc.
[0020] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0021] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0022] According to a first aspect of the present invention, the present invention provides a polyvinyl alcohol composition, the composition comprising polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer;
[0023] In parts by weight, the content of the polyvinyl alcohol is 65 to 85 parts, the content of the plasticizer is 12 to 30 parts, the content of the melt flow modifier is 2.5 to 4 parts by weight, and the content of the stabilizer is 0.5 to 1 part by weight.
[0024] In the present invention, the degree of polymerization of the polyvinyl alcohol is above 1700, the degree of alcoholysis is above 88 mol%, and the particle size is 0.3 mm to 0.8 mm. If the particle size of the polyvinyl alcohol purchased directly cannot meet the particle size range, the polyvinyl alcohol granules need to be crushed and sieved to a particle size of 0.3 mm to 0.8 mm.
[0025] According to the present invention, the plasticizer can be selected from at least one of water, glycerol, aminocaproic acid, urea and sorbitol. Preferably, the plasticizer is a mixture of at least one of glycerol, aminocaproic acid, urea and sorbitol and water, such as a mixture of water and glycerol, a mixture of water, glycerol and urea, a mixture of water, glycerol and aminocaproic acid, a mixture of water and urea, a mixture of water and sorbitol, and the amount of each component can be adjusted as needed, and water is deionized water.
[0026] In the present invention, the melt flow modifier can be selected from at least one of polyethylene glycol with a molecular weight of 400-1000, pullulan, talc, oleamide and erucamide.
[0027] According to the present invention, the stabilizer may be selected from at least one of pentaerythritol, sodium stearate, calcium stearate, citric acid and benzoic acid.
[0028] According to a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned polyvinyl alcohol composition, the preparation method comprising:
[0029] 1) uniformly mixing polyvinyl alcohol, a melt flow modifier and a stabilizer to obtain a mixture;
[0030] 2) The mixture and the plasticizer are added into an extruder to complete pre-softening, blending, plasticizing, and extrusion, and then air-cooled and pelletized to obtain a polyvinyl alcohol composition.
[0031] In step 1) of the present invention, mixing can be performed by mixing at room temperature using a high-speed mixer. In step 2), the extruder can be a twin-screw extruder with a side feeding device. The mixture obtained in step 1) is metered into the extruder through an automatic feeding device of the twin-screw extruder, and the plasticizer is metered into the extruder through the side feeding device of the twin-screw extruder. The polyvinyl alcohol plasticization can be achieved online, quickly and effectively, solving the problems of low efficiency and long processing cycle.
[0032] Preferably, the feed section of the extruder is not heated, the temperature of the other sections is 155° C. to 180° C., and the screw speed is 100 to 150 rpm. The other parameters can be selected by those skilled in the art with reference to the prior art, and will not be described in detail here.
[0033] The present invention can produce a polyvinyl alcohol composition with a particle size of 1.0-2.0 mm, a transparent or translucent spherical cylindrical appearance, a melt index of 10-30 g / 10 min (5 kg, 170° C.), a high pressure capillary melt viscosity of 100-500 Pa·S (shear rate 1000S -1 , 170℃).
[0034] According to a third aspect of the present invention, a method for preparing a polyvinyl alcohol film is provided. The film is prepared from the polyvinyl alcohol composition by melt extrusion and continuous biaxial stretching.
[0035] The film preparation of the present invention does not require special equipment, and can be continuously melt extruded and cast into sheets-biaxially stretched into films on conventional single-screw melt extrusion and casting-biaxially stretched equipment, thereby simplifying the process.
[0036] Preferably, the extrusion temperature is 170-190° C., the stretching temperature is 130-160° C., and the stretching ratio is 3.0-5.0 times.
[0037] According to a fourth aspect of the present invention, the present invention provides a polyvinyl alcohol film, which is prepared by the above-mentioned method for preparing the polyvinyl alcohol film.
[0038] The present invention can obtain a film with a thickness of 20 to 70 μm and a tensile strength greater than 80 MPa.
[0039] The substances and parameters not limited in the present invention can be selected according to the existing technology and belong to the conventional technical means in this field.
[0040] The present invention will be further described below with reference to the following examples, but is not limited to these examples.
[0041] In the following examples and comparative examples, the raw materials used and the testing methods of the relevant data are as follows:
[0042] Polyvinyl alcohol with a degree of polymerization of 1700 and a degree of alcoholysis of 88 mol % was purchased from Sichuan Vinylon Plant of Sinopec Group.
[0043] Polyvinyl alcohol having a degree of polymerization of 1700 and a degree of alcoholysis of 92 mol % was purchased from Sinopec Great Wall Energy Chemical (Ningxia) Co., Ltd.
[0044] Polyvinyl alcohol with a polymerization degree of 1700 and an alcoholysis degree of 95 mol % was purchased from Sichuan Vinylon Plant of Sinopec Group.
[0045] Polyvinyl alcohol with a polymerization degree of 2200 and an alcoholysis degree of 99 mol % was purchased from Sinopec Great Wall Energy Chemical (Ningxia) Co., Ltd.
[0046] Polyvinyl alcohol with a polymerization degree of 2400 and an alcoholysis degree of 99 mol % was purchased from Sichuan Vinylon Plant of Sinopec Group.
[0047] Polyvinyl alcohol with a polymerization degree of 1700 and an alcoholysis degree of 99 mol % was purchased from Sinopec Great Wall Energy Chemical (Ningxia) Co., Ltd.
[0048] Glycerol: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0049] Sorbitol: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0050] Urea: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0051] Aminocaproic acid: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0052] Polyethylene glycol: molecular weight 400, analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0053] Polyethylene glycol: molecular weight 1000, analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0054] Pullulan: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0055] Oleic acid amide: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0056] Erucamide: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0057] Talc: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0058] Pentaerythritol: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0059] Citric acid: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0060] Calcium stearate: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0061] Sodium stearate: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0062] Benzoic acid: analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0063] 1. The melt index of the polyvinyl alcohol composition was measured using a ZRZ1452 melt flow rate tester produced by Mester Industrial Systems (China) Co., Ltd., under the conditions of 5 kg and 170°C.
[0064] 2. The high pressure capillary melt viscosity of the polyvinyl alcohol composition was measured using a Rosand RH7D high pressure capillary rheometer from Malvern, UK, at a shear rate of 1000 s. -1 , temperature 170℃.
[0065] 3. The mechanical properties of polyvinyl alcohol biaxially stretched films were tested using an RGL-10 electronic universal testing machine produced by Rigel Instruments Co., Ltd.
[0066] Example 1
[0067] A polyvinyl alcohol composition, comprising polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer; in parts by weight, the polyvinyl alcohol content is 85 parts, the plasticizer content is 12 parts, the melt flow modifier content is 2.5 parts, and the stabilizer content is 0.5 parts. The degree of polymerization of the polyvinyl alcohol is 1700, the alcoholysis degree is 88 mol%, the particle size is 0.3 mm (average particle size), the plasticizer is a mixture of 5 parts by weight of water and 7 parts by weight of glycerol, the melt flow modifier is polyethylene glycol with a molecular weight of 400, and the stabilizer is pentaerythritol.
[0068] The polyvinyl alcohol crushed to an average particle size of 0.3 mm in a high-speed pulverizer is blended with a melt flow modifier and a stabilizer in a high mixer at room temperature, and the mixture is metered into the extruder through an automatic feeding device of a twin-screw extruder; the plasticizer that is stirred and mixed evenly is metered into the extruder through a side feeding device of a twin-screw extruder; each component is pre-softened, blended, plasticized, and extruded in the extruder, and then air-cooled at room temperature and pelletized by a pelletizer to obtain a polyvinyl alcohol composition. The temperatures of each section of the twin-screw extruder are: room temperature -175℃-180℃-180℃-180℃-180℃-170℃, and the rotation speed is 140rpm. The performance parameters of the obtained polyvinyl alcohol composition are shown in Table 1.
[0069] The polyvinyl alcohol composition was continuously melt extruded and cast into a sheet and biaxially stretched on a conventional single screw melt extrusion casting and biaxial stretching equipment, with an extrusion temperature of 190°C, a stretching temperature of 160°C, and a stretching ratio of 3.0. The performance parameters of the film are shown in Table 1.
[0070] Example 2
[0071] A polyvinyl alcohol composition, comprising polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer; in parts by weight, the polyvinyl alcohol content is 65 parts, the plasticizer content is 30 parts, the melt flow modifier content is 4 parts, and the stabilizer content is 1 part. The degree of polymerization of the polyvinyl alcohol is 1700, the degree of alcoholysis is 92 mol%, the particle size is 0.8 mm (average particle size), the plasticizer is a mixture of 15 parts by weight of water and 15 parts by weight of sorbitol, the melt flow modifier is amylopectin, and the stabilizer is citric acid.
[0072] The polyvinyl alcohol crushed to an average particle size of 0.8 mm in a high-speed pulverizer is blended with a melt flow modifier and a stabilizer in a high mixer at room temperature, and the mixture is metered into the extruder through an automatic feeding device of a twin-screw extruder; the plasticizer that is stirred and mixed evenly is metered into the extruder through a side feeding device of a twin-screw extruder; each component is pre-softened, blended, plasticized, and extruded in the extruder, and then air-cooled at room temperature and pelletized by a pelletizer to obtain a polyvinyl alcohol composition. The temperatures of each section of the twin-screw extruder are: room temperature -160℃-165℃-165℃-165℃-165℃-155℃, and the rotation speed is 100rpm. The performance parameters of the obtained polyvinyl alcohol composition are shown in Table 1.
[0073] The polyvinyl alcohol composition was continuously melt extruded and cast into a sheet and biaxially stretched on a conventional single screw melt extrusion casting and biaxial stretching equipment, with an extrusion temperature of 170°C, a stretching temperature of 150°C, and a stretching ratio of 5.0. The performance parameters of the film are shown in Table 1.
[0074] Example 3
[0075] A polyvinyl alcohol composition, comprising polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer; in parts by weight, the content of the polyvinyl alcohol is 75 parts, the content of the plasticizer is 21.2 parts, the content of the melt flow modifier is 3 parts, and the content of the stabilizer is 0.8 parts. The degree of polymerization of the polyvinyl alcohol is 1700, the degree of alcoholysis is 95 mol%, the particle size is 0.5 mm (average particle size), the plasticizer is a mixture of 8 parts by weight of water and 13.2 parts by weight of urea, the melt flow modifier is oleamide, and the stabilizer is calcium stearate.
[0076] The polyvinyl alcohol crushed to an average particle size of 0.5 mm in a high-speed pulverizer is blended with a melt flow modifier and a stabilizer in a high mixer at room temperature, and the mixture is metered into the extruder through an automatic feeding device of a twin-screw extruder; the plasticizer that is stirred and mixed evenly is metered into the extruder through a side feeding device of a twin-screw extruder; each component is pre-softened, blended, plasticized, and extruded in the extruder, and then air-cooled at room temperature and pelletized by a pelletizer to obtain a polyvinyl alcohol composition. The temperatures of each section of the twin-screw extruder are: room temperature -170℃-175℃-175℃-175℃-175℃-160℃, and the rotation speed is 120rpm. The performance parameters of the obtained polyvinyl alcohol composition are shown in Table 1.
[0077] The polyvinyl alcohol composition was continuously melt extruded and cast into a sheet and biaxially stretched on a conventional single screw melt extrusion casting and biaxial stretching equipment, with an extrusion temperature of 180°C, a stretching temperature of 155°C, and a stretching ratio of 3.5 times. The performance parameters of the film are shown in Table 1.
[0078] Example 4
[0079] A polyvinyl alcohol composition, comprising polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer; in parts by weight, the polyvinyl alcohol content is 70 parts, the plasticizer content is 25.5 parts, the melt flow modifier content is 4 parts, and the stabilizer content is 0.5 parts. The degree of polymerization of the polyvinyl alcohol is 2200, the alcoholysis degree is 99 mol%, the particle size is 0.3 mm (average particle size), the plasticizer is a mixture of 15 parts by weight of water, 10 parts by weight of glycerol and 0.5 parts by weight of aminocaproic acid, the melt flow modifier is erucamide, and the stabilizer is pentaerythritol.
[0080] The polyvinyl alcohol crushed to an average particle size of 0.3 mm in a high-speed pulverizer is blended with a melt flow modifier and a stabilizer in a high mixer at room temperature, and the mixture is metered into the extruder through an automatic feeding device of a twin-screw extruder; the plasticizer that is stirred and mixed evenly is metered into the extruder through a side feeding device of a twin-screw extruder; each component is pre-softened, blended, plasticized, and extruded in the extruder, and then air-cooled at room temperature and pelletized by a pelletizer to obtain a polyvinyl alcohol composition. The temperatures of each section of the twin-screw extruder are: room temperature -180℃-180℃-180℃-180℃-180℃-175℃, and the rotation speed is 130rpm. The performance parameters of the obtained polyvinyl alcohol composition are shown in Table 1.
[0081] The polyvinyl alcohol composition was continuously melt extruded and cast into a sheet and biaxially stretched on a conventional single screw melt extrusion casting and biaxial stretching equipment, with an extrusion temperature of 190°C, a stretching temperature of 160°C, and a stretching ratio of 3.5 times. The performance parameters of the film are shown in Table 1.
[0082] Example 5
[0083] A polyvinyl alcohol composition, comprising polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer; in parts by weight, the polyvinyl alcohol content is 65 parts, the plasticizer content is 30 parts, the melt flow modifier content is 4 parts, and the stabilizer content is 1 part. The degree of polymerization of the polyvinyl alcohol is 2400, the alcoholysis degree is 99 mol%, the particle size is 0.3 mm (average particle size), the plasticizer is a mixture of 20 parts by weight of water and 10 parts by weight of glycerol, the melt flow modifier is 3 parts by weight of polyethylene glycol with a molecular weight of 1000 and 1 part by weight of talc, and the stabilizer is sodium stearate.
[0084] The polyvinyl alcohol crushed to an average particle size of 0.3 mm in a high-speed pulverizer is blended with a melt flow modifier and a stabilizer in a high mixer at room temperature, and the mixture is metered into the extruder through an automatic feeding device of a twin-screw extruder; the plasticizer that is stirred and mixed evenly is metered into the extruder through a side feeding device of a twin-screw extruder; each component is pre-softened, blended, plasticized, and extruded in the extruder, and then air-cooled at room temperature and pelletized by a pelletizer to obtain a polyvinyl alcohol composition. The temperatures of each section of the twin-screw extruder are: room temperature -170℃-175℃-175℃-175℃-175℃-170℃, and the rotation speed is 150rpm. The performance parameters of the obtained polyvinyl alcohol composition are shown in Table 1.
[0085] The polyvinyl alcohol composition was continuously melt extruded and cast into a sheet and biaxially stretched on a conventional single screw melt extrusion casting and biaxial stretching equipment, with an extrusion temperature of 185°C, a stretching temperature of 160°C, and a stretching ratio of 3.0. The performance parameters of the film are shown in Table 1.
[0086] Example 6
[0087] A polyvinyl alcohol composition, comprising polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer; in terms of weight, the polyvinyl alcohol content is 80 parts, the plasticizer content is 16.5 parts, the melt flow modifier content is 3 parts, and the stabilizer content is 0.5 parts. The degree of polymerization of the polyvinyl alcohol is 1700, the alcoholysis degree is 99 mol%, the particle size is 0.6 mm (average particle size), the plasticizer is a mixture of 5 parts by weight of water, 10 parts by weight of glycerol and 1.5 parts by weight of urea, the melt flow modifier is 2 parts by weight of polyethylene glycol with a molecular weight of 400 and 1 part by weight of erucamide, and the stabilizer is benzoic acid.
[0088] The polyvinyl alcohol crushed to an average particle size of 0.6 mm in a high-speed pulverizer is blended with a melt flow modifier and a stabilizer in a high mixer at room temperature, and the mixture is metered into the extruder through an automatic feeding device of a twin-screw extruder; the plasticizer that is stirred and mixed evenly is metered into the extruder through a side feeding device of a twin-screw extruder; each component is pre-softened, blended, plasticized, and extruded in the extruder, and then air-cooled at room temperature and pelletized by a pelletizer to obtain a polyvinyl alcohol composition. The temperatures of each section of the twin-screw extruder are: room temperature -165℃-170℃-170℃-170℃-170℃-170℃, and the rotation speed is 110rpm. The performance parameters of the obtained polyvinyl alcohol composition are shown in Table 1.
[0089] The polyvinyl alcohol composition was continuously melt extruded and cast into a sheet and biaxially stretched on a conventional single screw melt extrusion casting and biaxial stretching equipment, with an extrusion temperature of 175°C, a stretching temperature of 150°C, and a stretching ratio of 4.0. The performance parameters of the film are shown in Table 1.
[0090] Example 7
[0091] Same as Example 1, except that the plasticizer used is 12 parts by weight of water. The performance parameters of the obtained composition and film are shown in Table 1.
[0092] Example 8
[0093] Same as Example 1, except that the plasticizer used is 12 parts by weight of propylene glycol. The performance parameters of the obtained composition and film are shown in Table 1.
[0094] Comparative Example 1
[0095] The same as Example 1, except that the composition does not contain a plasticizer. The composition cannot be thermoplastically extruded.
[0096] Comparative Example 2
[0097] Same as Example 1, except that the composition does not contain a melt flow modifier. The performance parameters of the obtained composition and film are shown in Table 1.
[0098] Comparative Example 3
[0099] The same as Example 1, except that the composition does not contain a stabilizer. The performance parameters of the obtained composition and film are shown in Table 1.
[0100] Table 1
[0101]
[0102] It can be seen from the results of the embodiments and comparative examples that the polyvinyl alcohol composition of the present invention has a moderate melt viscosity and melt index, so that the processing performance is good during the extrusion process, the film forming property is good during the film stretching process, and the film surface is uniform; and the biaxially stretched film prepared by the polyvinyl alcohol composition and the film preparation method of the present invention has good film tensile strength, which can be greater than 80MPa.
[0103] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A polyvinyl alcohol composition, characterized in that The composition contains polyvinyl alcohol, a plasticizer, a melt flow modifier and a stabilizer; In parts by weight, the content of the polyvinyl alcohol is 65 to 85 parts, the content of the plasticizer is 12 to 30 parts, the content of the melt flow modifier is 2.5 to 4 parts by weight, and the content of the stabilizer is 0.5 to 1 part by weight.
2. The polyvinyl alcohol composition according to claim 1, wherein The polyvinyl alcohol has a polymerization degree of more than 1700, an alcoholysis degree of more than 88 mol %, and a particle size of 0.3 mm to 0.8 mm.
3. The polyvinyl alcohol composition according to claim 1, wherein The plasticizer is selected from at least one of water, glycerol, aminocaproic acid, urea and sorbitol; Preferably, the plasticizer is a mixture of at least one of glycerol, aminocaproic acid, urea and sorbitol and water.
4. The polyvinyl alcohol composition according to claim 1, wherein The melt flow modifier is selected from at least one of polyethylene glycol with a molecular weight of 400-1000, pullulan, talc, oleamide and erucamide.
5. The polyvinyl alcohol composition according to claim 1, wherein The stabilizer is selected from at least one of pentaerythritol, sodium stearate, calcium stearate, citric acid and benzoic acid.
6. The method for preparing the polyvinyl alcohol composition according to any one of claims 1 to 5, characterized in that: The preparation method comprises: 1) uniformly mixing polyvinyl alcohol, a melt flow modifier and a stabilizer to obtain a mixture; 2) The mixture and the plasticizer are added into an extruder to complete pre-softening, blending, plasticizing, and extrusion, and then air-cooled and pelletized to obtain a polyvinyl alcohol composition.
7. The method for preparing the polyvinyl alcohol composition according to claim 6, wherein: The feed section of the extruder is not heated, the temperature of the other sections is 155°C to 180°C, and the screw speed is 100 to 150 rpm.
8. A method for preparing a polyvinyl alcohol film, characterized in that: The film is prepared from the polyvinyl alcohol composition according to any one of claims 1 to 5 by melt extrusion and continuous biaxial stretching.
9. The method for preparing a polyvinyl alcohol film according to claim 8, wherein: The extrusion temperature is 170-190°C, the stretching temperature is 130-160°C, and the stretching ratio is 3.0-5.0 times.
10. A polyvinyl alcohol film, characterized in that: The polyvinyl alcohol film is prepared by the method for preparing the polyvinyl alcohol film according to claim 8 or 9.
Citation Information
Patent Citations
A blow-molded polyvinyl alcohol film and its preparation method
CN106189010B
Polyvinyl alcohol film, polyvinyl alcohol composition, and preparation method of polyvinyl alcohol film
CN109721904A
Polyvinyl alcohol film, polyvinyl alcohol composition, and preparation method of polyvinyl alcohol film
CN109721905A
Plasticizer, polyvinyl alcohol composition, polyvinyl alcohol film and preparation method thereof
CN109721910A
Reactive extrusion method biaxially oriented polyvinyl alcohol film and preparation method thereof
CN114907657A